Exploring potentials of snakehead fishes (Channidae) of Northeast India with emphasis on their ornamental value and conservation status: Snakehead fishes (Channidae) of Northeast India - Sharma, Niti; Kumar Sarkar, Uttam; Yengkokpam, Sona; Bordoloi, Dipongkur; Chandra Ray, Bipul; Kumar Das, Basanta (Journal of the Inland Fisheries Society of India, 2023)
Northeastern region of India has a rich diversity of Channa species with high endemism, and both food and ornamental values. At present 17 species of snakehead are identified from Northeast region having beautiful body and fin coloration. Among them, 5 species from Assam, 2 each from Arunachal Pradesh and Mizoram, one from Manipur and 3 recently discovered species from Meghalaya are endemic to the region. In international ornamental fish trade, snakehead from this region has huge market demand a piece of : Channa barca fetches several thousand USD. The most frequently exported species C. stewartii (Assamese snakehead) along with C. bleheri (Rainbow snakehead) are categorized as Near Threatened under IUCN while C. aurantimaculata (Golden cobra snakehead) has high demand and market price. Wild caught snakehead contributes nearly 90% of live ornamental fish export, mainly via West Bengal to other Asian and European countries. Although most of the species are categorized as Least Concern and Data Deficient, they are at high risk due to over-exploitation, illegal fishing and habitat destruction. In this review the current status and potentials of the wild population have been explored, several issues have been highlighted and effective conservation measures are discussed.